Islam and Transportation Order: The Masalih Mursalah as Solution for Traffic Congestion in Jakarta, Indonesia - Muslihan; Wahyudhi, Johan; Multazam, Dawam (Hikmatuna : Journal for Integrative Islamic Studies, 2025)
This study explores how Islamic teachings can contribute to the creation of a regulated and sustainable transportation system amid the challenges of urbanisation and population growth. The research method used is a qualitative approach with an analysis of Islamic law (fiqh) focusing on masalih mursalah. Data was collected through a literature review of classical and contemporary Islamic literature, transportation policies, and empirical observations of traffic conditions in Jakarta. The analysis was conducted by integrating the principles of masalih mursalah with empirical data to formulate relevant solutions. The study also considered social and environmental aspects within the framework of Sharia law. The findings indicate that masalih mursalah can serve as a basis for Islamic transportation policies, such as the development of affordable public transportation, zone-based restrictions on private vehicles, and public education on traffic discipline as a solution to urban life. The results of this study are important as a paradigm for resolving Jakarta's chronic traffic congestion problem.